Silk, slaves, and stupas: material culture of the Silk Road - Whitfield, Susan (University of California Press, 2018)
"Following her bestselling Life Along the Silk Road, Susan Whitfield widens her exploration of the great cultural highway with another captivating portrait through the experience of things. Silk, Slaves, and Stupas tells the stories of ten very different objects, considering their interaction with the peoples and cultures of the Silk Road--those who made them, carried them, received them, used them, sold them, worshipped them, and, in more recent times, bought them, conserved them, and curated them. From a delicate pair of earrings from a steppe tomb to a massive stupa deep in Central Asia, a hoard of Kushan coins stored in an Ethiopian monastery to a Hellenistic glass bowl from a southern Chinese tomb, and a fragment of Byzantine silk wrapping the bones of a French saint to a Bactrian ewer depicting episodes from the Trojan War, these objects show us something of the cultural diversity and interaction along these trading routes of Afro-Eurasia. Exploring the labor, tools, materials, and rituals behind these various objects, Whitfield infuses her narrative with delightful details as the objects journey through time, space, and meaning. Silk, Slaves, and Stupas is a lively and unique approach to understanding the Silk Road and the cultural, economic, and technical changes of the late antiquity and medieval periods"--Provided by publisher